The activity level of follicular helper T cells in the peripheral blood of osteosarcoma patients is associated with poor prognosis. Issue 2 (1st February 2022) - Lu, Jianshu; Kang, Xiuqin; Wang, Zhitao; Zhao, Gang; Jiang, Baoen
ABSTRACT: Osteosarcoma (OS) is solid tumors with high malignancy and incidence starting in the bones. OS pathogenesis has been proved to be closely associated with immune imbalance, and follicular helper T cells (Tfh) significantly affect host humoral immune homeostasis. However, there are few reports on the effect of Tfh cell activation on the prognosis of OS patients. Hence, this investigation on the changes in the proportion of peripheral blood Tfh cells in OS patients, and the relationship between their activity level and OS prognosis. We collected peripheral blood from patients with OS, benign bone tumor (BT group) and healthy subjects (Healthy group), respectively. The number of CD4 + CXCR5 + Tfh cell in peripheral blood was measured by flow cytometry and correlation analysis between its activity and OS clinicopathological characteristics was carried out. The data showed that in comparison with the BT and Healthy groups, higher proportion and activation level of peripheral blood CD4 + CXCR5 + Tfh cells in CD4 + T cells were found in the OS group. In OS patients, increases of the proportion and activity level of Tfh cells were associated with poorly differentiated OS and tumor metastasis. Additionally, Kaplan-Meier and Cox regression analysis showed a longer overall survival in patients with low proportion of peripheral blood CD4 + CXCR5 + Tfh cells in CD4 + T cells, and their activation level may be a prognostic factor in OS patients. In conclusion, peripheral blood CD4 + CXCR5 + Tfh cell activation in OS patients was associated with a poor prognosis. This study provided ideas for improving the clinical treatment of OS patients. Graphical abstract: uf0001